Pengembangan Video pembelajaran Fisika Dengan Menggunakan pendekatan STEM Pada Materi Pengukuran Di SMAN 1 Muaro Jambi - Alrizal; Firdaus Firdaus; Haerul Pathoni (PendIPA Journal of Science Education, 2023)
The problem that is often encountered in learning at school, especially physics subjects, is the large number of students who say physics subjects are difficult to understand and are less interested in physics subjects, This is due to the not optimal learning media used by teachers, causing students not to understand the concepts and not interested in physics lessons. This lack of interest can be overcome with videos, so learning videos are needed that can increase students' understanding of concepts and learning interests. This study aimed to develop physics learning videos based on the STEM approach to measurement material. This research method uses a research and development design with a 4D development model. The subjects in this study were 30 students in class XI MIPA 1 at SMA Negeri 1 Muaro Jambi who had studied measurement material. This study used data collection in the form of initial needs questionnaires, interviews, media expert validation questionnaires and material experts as well as student response questionnaires. From the results of this study the media validation stage I obtained a score of 80.91% and stage II obtained a score of 97.36%. In material validation I obtained a score of 81.94% and stage II obtained a score of 96.52% and student responses to all indicators obtained a score of 83.86%. This study concludes that physics learning videos based on the STEM approach in measurement materials meet the eligibility criteria, which are very valid and very effective for learning physics measurement materials.